Concomitant Anti-hepatitis C positivity among family members of thalassemic patients - Hameed, Dawood S.; Raham, Tareef F.; Abdul wahid, Salwa Sh. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: This study was carried out from first of June 2008 till first of June 2009 at thallassemia center Diyala governorate on families who have more than one affected member with thalassemia and other member who also gives positive results for hepatitis C infection in addition to the index (infected) case. Material and methods: The study sample includes (13) families with (13) index cases who test positive for anti-hepatitis C antibody. Each family have at least two patients with thalassemia, the overall number is (29). Results: This study reveals that 76.92% (10 families) have at least one more member in the same family who also test positive for anti-hepatitis C antibody. Prevalence after exclusion of index cases is 68.75%. Conclusion: Anti-hepatitis C antibody is high among thalassemic siblings and routes of transmission of infections other than blood transfusion should be considered among thalassemic siblings.